The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1993
DOI: 10.1007/bf01256549
|View full text |Cite
|
Sign up to set email alerts
|

Host-plant green-leaf volatiles synergize the synthetic sex pheromones of the corn earworm and codling moth (Lepidoptera)

Abstract: Summary. The capture of adult male moths in female sex pheromone traps of two key agricultural pests, the corn earworm (Helicoverpa zea) and the codling moth (Cydia pomonella), is enhanced or synergized by a certain group of host-plant volatiles, the "green-leaf volatiles" (GLVs). Since female adults of both species call and release their sex pheromones while perched upon the leaves of their host-plants, the volatile constituents from the leaves of a number of host-plants were compared. Sex pheromone traps con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(121 citation statements)
references
References 53 publications
(50 reference statements)
3
115
1
2
Order By: Relevance
“…In contrast, in ßight-tunnel trials male European berry moth did not orient to grapes or other grape tissue whereas females did (Masante-Roca et al 2007). However, there is a growing body of evidence that male moths of a signiÞcant number of species are able to perceive and respond to host plant volatiles and in some cases, the addition of plant volatile cues with sex pheromone can result in increased capture of males (Light et al 1993, Landolt and Phillips 1997, Yang et al 2004, Schmidt-Bü sser et al 2009 but see Trimble and El-Sayed 2005). Indeed, a more recent study showed that male L. botrana oriented to their host plant volatiles (Von Arx et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, in ßight-tunnel trials male European berry moth did not orient to grapes or other grape tissue whereas females did (Masante-Roca et al 2007). However, there is a growing body of evidence that male moths of a signiÞcant number of species are able to perceive and respond to host plant volatiles and in some cases, the addition of plant volatile cues with sex pheromone can result in increased capture of males (Light et al 1993, Landolt and Phillips 1997, Yang et al 2004, Schmidt-Bü sser et al 2009 but see Trimble and El-Sayed 2005). Indeed, a more recent study showed that male L. botrana oriented to their host plant volatiles (Von Arx et al 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Pear ester attracts males and females and has been shown to mediate the location of food sources and oviposition sites Landolt et al, 2007;Light et al, 2001). Butyl hexanoate, a component of ripe apple headspace, attracts mated females Hern and Dorn, 2004), whereas (Z)3-hexenol enhances the attraction of males toward sex pheromone (Light et al, 1993;Yang et al, 2004). In contrast to males, the sesquiterpenes (E,E)-a-farnesene and (E)-bfarnesene elicited strong responses in female AL neurons (Tables1, 2).…”
Section: Integration Of Behaviourally Relevant Chemical Cuesmentioning
confidence: 99%
“…Host odor enhancement of attraction responses of males to pheromones was reported in several insect orders Light et al, 1993;Fang and Zhang, 2002;Deng et al, 2004). Reddy and Guerrero (2000b) reported that the mixture of (Z )-3-hexenyl acetate with synthetic sex pheromone had a synergistic effect on the capture of P. xylostella moths in the field in comparison with synthetic sex pheromone alone.…”
Section: Introductionmentioning
confidence: 99%